2009
DOI: 10.1254/jphs.09033sc
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Substance P Release From Cultured Rat Primary Afferent Neurons by Zinc Ions

Abstract: Abstract. The present study was conducted to determine whether zinc ions are involved in the modulation of substance P release from cultured rat dorsal root ganglion (DRG) neurons. We show here that that lower concentrations (10 −8 -10 −7 M) of zinc ions may evoke an extracellular Ca 2+ influx through L-, N-, and T-type voltage-dependent Ca 2+ channels, thereby increasing the substance P release from cultured DRG neurons, but higher concentrations (10 −6 -10 −4 M) of zinc ions attenuate or even completely mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Additionally, a recent study indicated that Kyn released from the fat body induces the formation of zinc storage granules in Malpighian tubules, where 3-HK and the xanthurenic acid act as endogenous zinc chelators. 43 Considering that zinc is a known modulator of SP release, 44 , 45 humoral Kyn may also regulate Tk release through zinc homeostasis during disc repair.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study indicated that Kyn released from the fat body induces the formation of zinc storage granules in Malpighian tubules, where 3-HK and the xanthurenic acid act as endogenous zinc chelators. 43 Considering that zinc is a known modulator of SP release, 44 , 45 humoral Kyn may also regulate Tk release through zinc homeostasis during disc repair.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, particularly MMP‐9 [18,19], MMP‐2 [19], and MMP‐5 [20], have been strongly implicated in the pathogenesis of neuropathic pain. Zinc is also known to modulate the secretion of the pain‐associated neuropeptide substance P in afferent rat neurons [21], with high zinc concentrations strongly inhibiting the release of substance P. It is possible that gallium has a similar effect.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a variety of studies suggests that zinc modulation of calcium channels affects calcium influx and transmitter release. A study in rat dorsal root ganglion neurons found that low concentrations (10–100 nM) of zinc evoked an extracellular calcium influx through L-, N- and T-type voltage-gated calcium channels, thus, increasing the release of substance P; higher concentrations (1–100 μM) of zinc attenuated or completely masked these responses (Tang et al, 2009 ). In the hippocampus and amygdala, high-frequency stimulation with the membrane-impermeable zinc chelator CaEDTA present enhanced exocytosis (Minami et al, 2006 ; Takeda et al, 2007 , 2010 ).…”
Section: Zinc Modulation Of Voltage-gated Ion Channels With a Focus Omentioning
confidence: 99%